PERENCANAAN STRATEGIS SISTEM INFORMASI MANAJEMEN UNTUK TRANSFORMASI DIGITAL PENDIDIKAN ISLAM: SEBUAH TINJAUAN LITERATUR - Abd. Rahman Ambo' Dalle; Sugeng Listyo Prabowo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The landscape of Islamic education faces a paradoxical tension between the imperative of digital transformation and the mandate to preserve Islamic values. This study aims to develop a research roadmap through a systematic literature review (SLR) to consolidate findings, critique existing models, and identify strategic directions for planning a technology-smart and value-grounded Islamic Management Information System (MIS). The research method employs library research with thematic and critical analysis of selected literature from indexed databases (2019–2025). The analysis reveals three critical themes: (1) rigid and fragmented classical planning models fail to respond to digital disruption and tend to reduce the mission of education to pragmatic efficiency targets; (2) digitalization is trapped in a technocratic narrative that overlooks socio-spiritual value transformation, despite its success depending on cultural change and digital leadership; (3) the integration of Islamic values often remains formalistic and symbolic, thus requiring deconstruction toward critical recontextualization based on maqasid al-shariah. The study’s conclusion offers a paradigmatic reconstruction through a critical contextualization approach, the development of a Maqasid al-Shariah-based MIS governance model, and communal-oriented digital innovation. This roadmap recommends a future research agenda to test empirical hybrid models, develop contextual planning instruments, and deepen studies on Islamic digital leadership, in order to realize a relevant and transformative vision of Islamic education in the digital era.